2019
DOI: 10.1021/acs.jpclett.9b00759
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Optical Gain Threshold in Two-Dimensional CdSe Nanoplatelets by the Giant Oscillator Strength Transition Effect

Abstract: Two-dimensional CdSe nanoplatelets are promising lasing materials. Their large lateral areas reduce the optical gain threshold by increasing the oscillator strength and multiexciton lifetimes but also increase the gain threshold by requiring multiple band-edge excitons (>2) to reach the optical gain. We observe that the optical gain threshold of CdSe nanoplatelets at 4 K is ∼4-fold lower than that at room temperature. Transient absorption spectroscopy measurements indicate that the exciton center-of-mass coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 51 publications
3
83
0
Order By: Relevance
“…F A b s is proportional to the total platelet area and determines the pronounced exciton feature in the absorption spectrum, while F S t a r k is proportional to the coherence area of the localized exciton and is the relevant quantity to understand the radiative lifetime of the exciton. This result questions previously published estimates of the exciton area at room temperature of 96 nm 2 or 21 nm 2 for similar 4.5 ML nanoplatelets 19 , 20 . Such large coherence areas would yield significantly shorter room temperature radiative lifetimes than measured experimentally.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…F A b s is proportional to the total platelet area and determines the pronounced exciton feature in the absorption spectrum, while F S t a r k is proportional to the coherence area of the localized exciton and is the relevant quantity to understand the radiative lifetime of the exciton. This result questions previously published estimates of the exciton area at room temperature of 96 nm 2 or 21 nm 2 for similar 4.5 ML nanoplatelets 19 , 20 . Such large coherence areas would yield significantly shorter room temperature radiative lifetimes than measured experimentally.…”
Section: Discussionsupporting
confidence: 66%
“…Similar observations were made in the case of epitaxial quantum wells 17 , 18 , and attributed to the large in-plane coherence area of the exciton center-of-mass motion in these systems. Intriguingly, recent reports based on state-filling models proposed that even at room temperature, this coherence might be close to 100 nm 2 , a number that seems incompatible with the nanosecond radiative lifetime reported by various authors 19 21 . In addition, several studies indicated the potential for strong coupling of excitonic transitions with the light field at room temperature using 4.5 monolayer CdSe nanoplatelets, a feat that requires narrow transition lines with large oscillator strength 8 , 9 .…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Unlike in core‐only NPLs, thick‐shell NPLs could further extend the spatial separation of excitons in thickness dimensions, which lengthens the multiexciton state and gain lifetimes. As a result, the extremely long optical gain lifetime (>800 ps) of CdSe/CdS NPLs is ≈8 times larger than those previously reported core‐only NPLs (≈100 ps) and also near two times greater than those of conventional CdSe/CdS QDs (>400 ps) . Recently, such long optical gain lifetime (≈800 ps) is also reported in this novel CdSe/CdS@CdZnS core/crown@gradient‐alloyed shell colloidal quantum wells .…”
Section: Resultsmentioning
confidence: 49%